Upward mobility - Rakowski, Paul (Outlook : the journal of high-performance business)
Although the mobile commerce market is a reality today, its promise still eclipses its practicality. The growth of near-field communications technology is certainly one key to realizing that promise. But industry players now have to find the right ways to encourage merchants to participate.